Ayahuasca-assisted meaning reconstruction therapy for grief: a non-randomized clinical trial protocol - Sabucedo, Pablo; Andión, Oscar; Neimeyer, Robert A.; Soto-Angona, Oscar; Javkin, Julia; Haro, Josep Maria; Farré, Magi; González, Débora (Frontiers in Psychiatry, 2025)
BackgroundPsychotherapy for Prolonged Grief Disorder (PGD), a condition characterized by an intense and persistent grief response, has received increased attention over the past decades. Evidence-based approaches to prevent PGD are currently scarce, and not always effective. This paper introduces a protocol for a clinical trial exploring the effectiveness of a Meaning Reconstruction psychotherapy approach (MR) assisted with ayahuasca, a traditional indigenous medicine.MethodThe outlined protocol is a three-arm, non-randomized controlled trial focused on reducing normal and pathological grief symptoms, comparing the effectiveness of Ayahuasca-assisted MR therapy (A-MR), MR therapy alone (MR) and No Treatment (NT). At least 69 people who lost a first-degree relative during the prior year, and with a Texas Revised Inventory of Grief score up 39 (TRIG ≥ 40), will participate in the trial. Participants will be allocated to an A-MR (n ≥ 23), MR (n ≥ 23) or NT (n ≥ 23) group. Those from the A-MR and MR therapy groups will undergo a therapeutic process involving 9 sessions of online psychotherapy. In addition, the A-MR condition involves 2 group sessions of ayahuasca. The primary outcomes will be normal and pathological grief severity as measured by the TRIG and Traumatic Grief Inventory Self-Report (TGI-SR), administered at baseline, post-treatment, and 3-month follow up. Measures of quality of life, post-traumatic growth, meaning-made, psychological flexibility, and self-belief consistency will be also included. In addition, subjective effects of ayahuasca and acceptance-avoidance promoting effects will be assessed following ayahuasca administration. Finally, we will analyze the potential mediating effect of meaning-made, psychological flexibility and self-belief consistency in grief symptoms (as measured by the TRIG and TGI).DiscussionThis trial is the first to empirically examinate the potential of psychedelic-assisted psychotherapy for grief, as well as the potential processes of change that may account for it.Clinical trial registrationhttps://clinicaltrials.gov, identifier NCT06150859.